Computer supported collaborative learning: A business simulation activity using social media - CHUNG, Siyoung (Institutional Knowledge at Singapore Management University, 2015)
Social media are dramatically changing the way welive and make social relationships with others. While students areso immersed in social media in their daily life, social mediaadoption in classroom has been slow. Educators who wish toexperiment with social media for CSCL struggle to find ways toincorporate the expected benefits and advantages of social mediato teaching lessons. This paper reports on the experiences ofusing social media for a business case simulation activity in ahigher learning context. Drawing on a qualitative feedback andsocial media log data of 27 teams of 135 undergraduate students,this paper discusses the advantages and disadvantages of socialmedia as a CSCL tool in classroom, especially